Gambaran Umum Pengetahuan Keluarga tentang Penyakit Demam Berdarah Dengue - Toru, Veronika; Radandima, Ester; Noviana, Ineke; Kitu, Irene Febriany Mamo; Kaka, Mahendri Ega (JURNAL KESEHATAN PRIMER, 2021)
Background: Dengue Hemorrhagic Fever (DHF) is a health problem in tropical countries. DHF is an infectious disease caused by the dengue virus, (WHO) in 2021, around 390 million people in the world are infected with the Dengue virus per year. As many as 3.9 billion people in 128 countries are at risk of being infected with the Dengue virus with 70% of the risk being found in Asia. Objective: To determine the Overview of Family Knowledge About Dengue Hemorrhagic Fever in the Waingapu Health Center Work Area. Method: This type of research uses a descriptive method, namely a method to obtain an overview of family knowledge about Dengue Hemorrhagic Fever in Waingapu Village, the research subjects are families. The instrument in this study was a questionnaire containing 15 items of questions about knowledge about DHF. Results: From the results of the study, the results of the respondents' knowledge were obtained, namely those with good knowledge were 15 people (50%), and those with sufficient knowledge were 12 people (40%) and respondents with less knowledge were 3 people (10%).